Effects of neem (Azadirachta indica) and pawpaw [carica papaya) leaves supplementation on performance and carcass characteristics of broilers (2012)
A study was designed to investigate the combined effects of neem and pawpaw leaves supplementation on performance and carcass characteristics of broiler chickens from 14–56 days of age. 360 one day-old unsexed Arbor acre broiler chickens were randomly allotted to the following diets T1 (0% leaf meal), T2 (0.5% NLM), T3 (2% PLM), T4 (0.5% NLM+PLM), T5 (1% NLM+PLM) and T6 (2% NLM+PLM). Results obtained from the study indicated that supplementation of NLM and PLM improved the dressing percentages, the highest values of 89.29% and 87.55% were obtained for birds on T5 and T6 respectively which were significantly different (p<0.05) when compared with the value obtained from which was 76.83%. The eviscerated weight differs significantly across the treatments, birds on T5 and T6 had significantly better (p<0.05) results of 76.93% and 75.85% respectively compared to treatments 4 and 5 which had 69.33% and 73.13% respectively. Body weight gain, feed consumed and feed conversion ratio of the broiler chickens improved in the treatments fed diets supplemented with leaf meal although and there were no significant (P>0.05) differences.